2019
DOI: 10.1371/journal.pmed.1002805
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic tests, drug prescriptions, and follow-up patterns after incident heart failure: A cohort study of 93,000 UK patients

Abstract: Background Effective management of heart failure is complex, and ensuring evidence-based practice presents a major challenge to health services worldwide. Over the past decade, the United Kingdom introduced a series of national initiatives to improve evidence-based heart failure management, including a landmark pay-for-performance scheme in primary care and a national audit in secondary care started in 2004 and 2007, respectively. Quality improvement efforts have been evaluated within individual c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 24 publications
4
42
0
Order By: Relevance
“… 7 , 8 Randomized clinical trials have demonstrated the effectiveness of these treatments in reducing mortality and hospitalizations, and observational studies have shown that they are increasingly being used worldwide. 9 , 10 , 11 Despite this, several recent studies have reported that the decline in mortality rates among patients with heart failure has been stalling since the mid-2000s. 12 , 13 , 14 To our knowledge, the reasons underlying this apparent paradox are unknown.…”
Section: Introductionmentioning
confidence: 99%
“… 7 , 8 Randomized clinical trials have demonstrated the effectiveness of these treatments in reducing mortality and hospitalizations, and observational studies have shown that they are increasingly being used worldwide. 9 , 10 , 11 Despite this, several recent studies have reported that the decline in mortality rates among patients with heart failure has been stalling since the mid-2000s. 12 , 13 , 14 To our knowledge, the reasons underlying this apparent paradox are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In PLOS Medicine , Rahimi and colleagues report the results of a longitudinal analysis of diagnostic tests, drug prescriptions, and follow-up patterns in 93,000 individuals with heart failure in the UK [11]. The authors show convincingly that some aspects of care, such as the use of diagnostic testing and initiation of evidence-based therapies, have improved over time.…”
Section: Utilising Routinely Collected Healthcare Data In Heart Failurementioning
confidence: 99%
“…It is clear how such findings, if sufficiently robust, could be used to inform future targeted interventions. The study certainly provides us valuable retrospective insights into two major policy initiatives designed to improve standards in heart failure treatment focused on primary and secondary care [11]. The data show persuasively that both the ‘quality and outcomes framework’, a primary care reporting and incentives scheme, and the ‘national heart failure audit’ initiative, a secondary care reporting programme, changed behaviour, but that the outcomes were tied too tightly to specific measures and may have led to unintended consequences.…”
Section: Utilising Routinely Collected Healthcare Data In Heart Failurementioning
confidence: 99%
“…Secondly, prescribing of medications with proven prognostic benefit in heart failure remains suboptimal across all age groups, although treatment rates are improving over time . Many patients also do not receive the recommended combination or optimal dose of medications .…”
mentioning
confidence: 99%
“…Secondly, prescribing of medications with proven prognostic benefit in heart failure remains suboptimal across all age groups, although treatment rates are improving over time . Many patients also do not receive the recommended combination or optimal dose of medications . Older people may be at particular risk of not receiving these medications due to individual patient factors such as treatment intolerance, impaired renal function, or medication interactions.…”
mentioning
confidence: 99%